Exploring Childhood Lower Urinary Tract Symptoms (LUTS), Urinary Tract Infections (UTIs) and the Microbiome—A Systematic Review - Mauro Van den Ende; Laure Van de Steen; Karel Everaert; François Hervé; George Bou Kheir (Life)
Pediatric lower urinary tract symptoms (LUTS) are influenced by age and coexist with nocturnal enuresis (NE) and bladder-bowel dysfunction (BBD). Urinary tract infections (UTIs) are common and linked to LUTS, though the causal relationship remains unclear. This systematic review aims to analyze microbiome alterations in pediatric LUTS and UTIs. Methods: A systematic review was conducted following PRISMA guidelines. PubMed, Embase, and CINAHL databases were searched for studies analyzing gut and urinary microbiomes in pediatric patients with LUTS and UTIs. Quality assessment was performed using the QUADOMICS checklist. Results: Nine studies published between 2018 and 2024 were included; seven out of nine studies employed prospective designs. Six hundred nineteen patients (44.3% pathology groups, 55.7% controls) were analyzed, with microbiome sequencing performed on stool samples in four studies and urine samples in five studies. UTIs and BBD were associated with reduced alpha diversity and distinct bacterial compositions, while beta diversity analyses revealed distinct clustering of microbiome compositions between affected and healthy groups. The gut microbiome of UTI patients showed alterations in Actinobacteria and Proteobacteria abundance, while voiding dysfunction (VD) was linked to the presence of Fusobacterium nucleatum, Clostridium difficile, and Bacteroides clarus without significant VDSS correlation. Conclusion: This systematic review reveals microbial alterations in pediatric LUTS and UTIs, with lower urinary diversity in UTI patients and sex-specific differences post-puberty. Microbiome-based interventions may offer novel therapeutic strategies for LUTS and UTIs.